2019
DOI: 10.1002/smll.201902081
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Cooperative Effects of Pyridinic and Graphitic Nitrogen Sites at Metal‐Free N‐Doped Carbon Electrocatalysts for the Oxygen Reduction Reaction

Abstract: Metal-free carbon electrodes with well-defined composition and smooth topography were prepared via sputter deposition followed by thermal treatment with inert and reactive gases. XPS and Raman spectroscopies show that three carbons of similar N/C content that differ in Nsite composition were thus prepared: an electrode consisting of almost exclusively graphitic-N (NG), an electrode with predominantly pyridinic-N (NP) and one with ca. 1:1 NG:NP composition. These materials were used as model systems to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 54 publications
0
57
0
Order By: Relevance
“…[38][39][40] The high-resolution N 1s spectrum ( Figure S5B) could be deconvoluted into five peaks centered at 398.1, 399.1, 399.8, 401.2, and 403.1 eV, respectively, corresponding to pyridinic-N, Co-N x , pyrrolic N, graphitic-N, and oxidized graphitic-N. 41,42 Compared with C-C@NC (without Fe substitution) and C@NC (without Fe and Cu substitution), FC-C@NC exhibited energy shifts in binding energies in Co 2p and N 1s spectra (a positive shift of about 0.6 eV for Co 2p and a negative shift of about 0.6 eV for N 1s, as shown in Figure 3E,F), indicating Fe and Cu substitution into Co sites had a little influence on the chemical states of Co and N. In addition, FC-C@NC contained higher N content (10.8%), and the content of pyridinic N and graphitic-N was 60% of the total N content, which was supposed to be beneficial for ORR process. 43 The electrocatalytic activities of all samples for ORR were first evaluated using a three-electrode configuration cell in alkaline solution (0.1 M KOH) at room temperature. As shown in Figure S6, no redox peak was observed for FC-C@NC in Ar-saturated KOH solution, while a welldefined cathodic peak (0.85 V vs RHE and all the potentials in this study were compared with RHE) was observed in O 2 -saturated KOH solution, predicting its effective ORR catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] The high-resolution N 1s spectrum ( Figure S5B) could be deconvoluted into five peaks centered at 398.1, 399.1, 399.8, 401.2, and 403.1 eV, respectively, corresponding to pyridinic-N, Co-N x , pyrrolic N, graphitic-N, and oxidized graphitic-N. 41,42 Compared with C-C@NC (without Fe substitution) and C@NC (without Fe and Cu substitution), FC-C@NC exhibited energy shifts in binding energies in Co 2p and N 1s spectra (a positive shift of about 0.6 eV for Co 2p and a negative shift of about 0.6 eV for N 1s, as shown in Figure 3E,F), indicating Fe and Cu substitution into Co sites had a little influence on the chemical states of Co and N. In addition, FC-C@NC contained higher N content (10.8%), and the content of pyridinic N and graphitic-N was 60% of the total N content, which was supposed to be beneficial for ORR process. 43 The electrocatalytic activities of all samples for ORR were first evaluated using a three-electrode configuration cell in alkaline solution (0.1 M KOH) at room temperature. As shown in Figure S6, no redox peak was observed for FC-C@NC in Ar-saturated KOH solution, while a welldefined cathodic peak (0.85 V vs RHE and all the potentials in this study were compared with RHE) was observed in O 2 -saturated KOH solution, predicting its effective ORR catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Although platinumbased materials offer superior catalytic activity in ORR, scare reserve and low methanol tolerance of platinum prompt development of nonprecious alternatives such as transition metal alloys, metal oxides and metal-free compounds. [20][21][22][23][24][25] The ORR activity of g-C 3 N 4 as a metal-free electrocatalyst was first reported by Lyth et al and at the same time, they suggested to mix the g-C 3 N 4 with carbon to overcome sluggish kinetics of the g-C 3 N 4 . [26] The strategy of compositing the g-C 3 N 4 with carbon materials brought a huge improvement in ORR activity of the g-C 3 N 4.…”
Section: Doi: 101002/smll201903572mentioning
confidence: 99%
“…Electrochemical oxygen reduction reaction (ORR) is a crucial process for renewable energy applications such as fuel cells, metal‐air batteries and solar cells. Although platinum‐based materials offer superior catalytic activity in ORR, scare reserve and low methanol tolerance of platinum prompt development of nonprecious alternatives such as transition metal alloys, metal oxides and metal‐free compounds . The ORR activity of g‐C 3 N 4 as a metal‐free electrocatalyst was first reported by Lyth et al and at the same time, they suggested to mix the g‐C 3 N 4 with carbon to overcome sluggish kinetics of the g‐C 3 N 4 .…”
mentioning
confidence: 99%
“…18,32 It has been reported that pyridinic and graphitic nitrogens play a vital role in the ORR catalytic activity. [33][34][35][36][37] According to Table 2, the combined amounts of pyridinic N and graphitic N account for 76.36, 62.73 and 56.28% of the total amounts of nitrogen of NEA, NA and NE, respectively. Consequently, NEA possesses both the highest level of total nitrogen and the largest amounts of pyridinic N and graphitic N among the four materials, suggesting its ability to operate as a high-performance ORR catalyst.…”
Section: Resultsmentioning
confidence: 99%